George Washington - D'Aulaire, Ingri, 1904-1980.; D'Aulaire, Edgar Parin, 1898-1986.; Eichenberg, Fritz, 1901-1990 (Garden City, N.Y., Doubleday, Doran, 1936)
A simple biography of Washington, telling of the major events in his life and stressing the upbringing that endowed him with the qualities of leadership.
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography -- Juvenile literature; Generals -- United States -- Biography -- Juvenile literature; Juvenile literature -- 1936.